The Impact of Various Factors on Improving Employee Performance - Hidayati, Firdausi Nur; Wijiastuti, Sri; Widodo, Zandra Dwanita (Forum Kerjasama Pendidikan Tinggi, 2025)
Employee performance is a key indicator in assessing the effectiveness and efficiency of an organization's operations, encompassing the quality and quantity of work achieved by employees in accordance with their responsibilities. This study aims to analyze the influence of (1) Workplace Facilities, (2) Workplace Discipline, (3) Compensation, and (4) Leadership on Employee Performance at BAPPERIDA of Wonogiri Regency, both partially and simultaneously. This quantitative research uses primary data. To ensure data quality, validity and reliability tests were conducted. The study employed a questionnaire that integrates several previously used questionnaires from prior research. The sampling technique used in this study was Total Sampling, involving 31 civil servant employees at BAPPERIDA of Wonogiri Regency. Data analysis was carried out using multiple linear regression. The results of the study revealed the following: Workplace facilities do not have a partial influence on employee performance, with a t-value of -1.791 and a significance level of 0.085. Workplace discipline has a significant partial influence on employee performance, with a t-value of 2.715 and a significance level of 0.012. Compensation has a significant partial influence on employee performance, with a t-value of 2.682 and a significance level of 0.013. Leadership has a significant partial influence on employee performance, with a t-value of 2.391 and a significance level of 0.024. Simultaneously, these four variables have a significant influence on employee performance, with a significance value of 0.001 (< 0.05). The coefficient of determination indicates that the regression model explains 79.6% of the variance in employee performance, leaving 20.4% attributable to variables not included or considered in this study.